The temperature dependence of the heliconical tilt angle in the twist-bend nematic phase of the odd dimer CB7CB. Issue 2 (13th November 2014) - Meyer, C.; Luckhurst, G. R.; Dozov, I.
Abstract : Precise birefringence measurements in large monodomains of the twist-bend nematic phase strongly support its heliconical structure and doubly degenerate handedness. Abstract : We report precise birefringence measurements in the nematic, N, and in the twist-bend nematic, NTB, phases of the odd liquid crystal dimer CB7CB. The birefringence results obtained in large monodomains of the NTB phase strongly support its heliconical structure with doubly degenerate handedness and provide the temperature dependence of the conical tilt angle, θ . The birefringence measured in planar wall defects separating the monodomains with opposite sign of the chirality suggests a splay-bend structure of the nematic in this region, enabling a smooth transition between the adjacent right- and left-handed heliconical domains.